PENGARUH KOMITMEN PROFESIONAL, LOCUS OF CONTROL, KESERIUSAN PELANGGARAN DAN SUKU BANGSA TERHADAP INTENSI WHISTLEBLOWING (Studi Empiris pada Pemerintahan Daerah DKI Jakarta) - Ridho, Muhammad Sidqi; Rini, Rini (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2016)
The purpose of this study was to examine the influence of professional commitment,locus of control, seriousness of wrongdoing and ethnic group on whistleblowingintentions. The respondents in this research is financial staff in working units of local government (SKPD) DKI Jakarta. The sample in this research were 39 financial staff in 7 working unit of local government (SKPD) DKI Jakarta. The method of determining the sample uses convenience sampling method. Methods of analysis to test the hypothesis is multiple regression analysis. The results showed that the seriousness of wrongdoing affect the whistleblowing intentions. However, professional commitment, locus of control and ethnic group have no effect on whistleblowing intentions.